Literary Education in early childhood: contradictions between what is promised and what is delivered - Simões Girotto, Cyntia Graziella Guizelim [UNESP]; de Souza, Renata Junqueira [UNESP]; Kanthack Hernandes, Elianeth Dias [UNESP]; Selfa, Moisés (Taylor & Francis, 2020)
This article presents the results of a comprehensive survey, carried out with 520 early childhood teachers from 68 Early Childhood Education (ECE) institutions located in the western region of the state of São Paulo, Brazil. The research aimed to verify the effects of the National School Library Program- PNBE–in the formation of readers. The PNBE was a government public policy to promote reading practice with young chiuldren from the beginning of the basic schooling stage (0–5 year-olds). Contradicting the intentions of the proposers of this policy, which was intended to distribute books and encourage reading, the research data indicate minimal circulation of Children’s Literature texts in institutions and the lack of knowledge of this material among educational managers. The outcome also points to the weaknesses in the initial and continued training of teachers as mediators of early childhood literary reading practices. The reflection presented in this paper points out the existing gap between what is proposed by public reading policies and actual practices implemented in schools concerning Literary Education in Early Childhood.
Keywords: Early childhood education; provision of books for children; public policies for reading; reading; training for teaching